RANCANG BANGUN APLIKASI PENGAMAN ISI FILE DOKUMEN DENGAN ALGORITMA RSA - Rakhmat Kurniawan (ALGORITMA : JURNAL ILMU KOMPUTER DAN INFORMATIKA, 2017)
Document security is one of the most important things in the exchange of data, especially the exchange of data in the virtual world in which there are many threats when the process is done. Data security, especially for text documents for an organization that assumes that the document is confidential (private and confidential). One aspect of security in a text document is its authenticity, form and contents must be in accordance with the intended by the author. Until now the cryptographic system is one solution to ensure the security of a data that is by encode the contents or content file the document becomes difficult content not even understood through the process of encryption and to recover the original information is done, the decryption process is accompanied by using the key correct. One of the most popular methods in cryptography is RSA, which to this day is very difficult to solve and will take a very long time. This method uses 2 (two) keys, namely public key and private key. Where the key length can be determined and adjusted to the desired level of security.Keywords: data security, RSA, cryptography